Influence of nanoparticles on liver tissue and hepatic functions: A review. (30th January 2020) - Cornu, Raphaël; Béduneau, Arnaud; Martin, Hélène
Abstract: Due to the increasing interest in nanotechnology in very large application fields, including biotechnology, electronics and food industries, humans are increasingly exposed to nanoparticles (NPs). Consequently, the question about the safety of these nanomaterials and their impact on human health is a legitimate concern. The liver is the primary organ of detoxification and is one of the tissues that is most exposed to NPs. When they reach the bloodstream, NPs are mainly internalized by liver cells. This review focuses on recent in vitro and in vivo studies addressing the effects of organic and inorganic NPs on the liver. Specifically, the impact of the NPs on hepatic enzyme activities, the inflammatory response and genotoxicity processes will be described. Depending on the physicochemical parameters of the NPs and the conditions of exposure, NPs could lead to global liver injury.